Requirements for the Personal and Professional Image of the Head of an Educational Institution and the Features of Its Creation - Oleksandra Marmaza; Olena Grechanyk (Pedagogical Discourse, 2025)
The article substantiates that in our time it is becoming important how the head positions himself and presents his organization; that the image is becoming a guarantee of his success and an important factor in the competitiveness of an educational organization. The emergence of new opportunities for the disclosure of professional potential requires the head of an educational institution to have the ability to self-improve and purposefully create his own image.The stated goal has been achieved: the features of the personal and professional image of the head of an educational institution in the context of the requirements for it have been revealed; the tasks have been completed: the importance of the head's image for effective management has been substantiated; the components of the image and the levels of its formation have been identified; the stages of its creation have been clarified.It has been established that the personal and professional image of a head is a set of features and characteristics that form his image as a specialist in the process of interaction with colleagues, students, social environment and the performance of official duties. The image is formed as a result of the synergistic effect of a set of personal and business qualities that characterize the leader. The following main components of the image of the head of an educational institution were identified and characterized: visual, communicative, personal and professional. According to the proposed components of the image of the head of an educational institution, the levels of formation of each of them were determined: low, critical, sufficient and optimal; a factor-criteria model was developed for assessing the personal and professional image of the leader. An algorithm for creating a personal and professional image of the leader was proposed, which is represented by 13 stages according to the logic of formation.This became possible through the comprehensive use of methods, in particular, theoretical ones: analysis of scientific, methodological and regulatory materials, synthesis, classification, comparison of the main concepts of imageology - to highlight the main ideas and provisions of the topic; systematization, generalization - to formulate conclusions; statistical information processing: construction of tables - for condensing and visualizing information.